2012
DOI: 10.3892/ol.2012.979
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch repair hMSH2, hMLH1, hMSH6 and hPMS2 mRNA expression profiles in precancerous and cancerous urothelium

Abstract: Abstract. Changes in the expression of the mismatch repair (MMR) genes hMSH2, hMLH1, hMSH6 and hPMS2 reflect dysfunction of the DNA repair system that may allow the malignant transformation of tissue cells. The aim of the present study was to address the mRNA expression profiles of the mismatch DNA repair system in cancerous and precancerous urothelium. This is the first study to quantify MMR mRNA expression by applying quantitative real-time PCR (qPCR) and translate the results to mRNA phenotypic profiles (r,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
1
10
0
1
Order By: Relevance
“…These findings suggest that miR-21-5p and hMSH2 might play roles in the radiation sensitivity of NSCLC and that inhibition of miR-21-5p might promote the radiation sensitivity of NSCLC through hMSH2. hMSH2 is an MMR gene, the dysfunction of which may cause malignant transformation of tumor cells [21]. In line with our results, Zhong Z reported that miR-21-5p is a key regulator of hMSH2 and modulates the cell cycle and viability by targeting hMSH2 in human lung cancer [16].…”
Section: Discussionsupporting
confidence: 75%
“…These findings suggest that miR-21-5p and hMSH2 might play roles in the radiation sensitivity of NSCLC and that inhibition of miR-21-5p might promote the radiation sensitivity of NSCLC through hMSH2. hMSH2 is an MMR gene, the dysfunction of which may cause malignant transformation of tumor cells [21]. In line with our results, Zhong Z reported that miR-21-5p is a key regulator of hMSH2 and modulates the cell cycle and viability by targeting hMSH2 in human lung cancer [16].…”
Section: Discussionsupporting
confidence: 75%
“…Again, the authors did not test if MSH6 was overexpressed as well. However, a number of studies suggest that MSH2 and MSH6 mRNA and protein expression in cancers are correlated to each other (Vageli et al 2013;Wagner et al 2016), as we found in certain tumors overexpressing both MSH2 and MSH6 ( Figure S2). Additionally, in their study of 115 oral squamous cell carcinoma samples, Wagner et al (2016) showed that many of these cancers exhibited overexpression of MSH2 or MSH6 alone, and a significant fraction showed cooverexpression of MSH2 and MSH6.…”
Section: Implications For Understanding Cancer Progressionmentioning
confidence: 55%
“…Although multiple diagnostic and prognostic markers have been identified for both lung and head and neck cancers [18,19], the precise molecular mechanisms involved in the development and progression of these malignancies remain unclear.We understand that a functional DNA repair mechanism that includes the recognition and repair of mismatch DNA errors during DNA replication is essential in eliminating the harmful effect of several environmental risk factors, such as NNK, on the exposed cells [20][21][22][23]. A number of studies have shown that reduced expression of mismatch DNA repair (MMR) genes increases the incidence of microsatellite instability [24][25][26][27], which is often found in head and neck cancer [28][29][30][31]. Other studies have also shown that reduced expression of MSH2 or MLH1 genes at the protein or mRNA levels is associated with poor survival and MSI in lung cancer [32][33][34].In addition, MMR deficiency appears to affect the effectiveness of chemotherapy in these cancers [34,35].…”
mentioning
confidence: 99%